Metabolic and Redox Biomarkers in Skeletal Muscle Underlie Physiological Adaptations of Two Estivating Anuran Species in a South American Semi-arid Environment - Moreira, Daniel C.; Carvajalino-Fernández, Juan M.; Navas, Carlos A.; de Carvalho, José E.; Hermes-Lima, Marcelo (Frontiers in Physiology, 2021)
The upregulation of endogenous antioxidant (i.e., preparation for oxidative stress, POS) is part of the biochemical responses underlying the adaptation of animals to adverse environments. Despite the phylogenetic diversity of animals in which POS has been described, most studies focus on animals under controlled laboratory conditions. To address this limitation, we have recently assessed the redox metabolism in the skeletal muscle of Proceratophrys cristiceps estivating under natural settings in the Caatinga. Here, we analyzed biochemical biomarkers in the muscle of another Caatinga species, Pleurodema diplolister, during the rainy (active) and dry (estivating frogs) seasons. We aimed to determine whether P. diplolister enhance its antioxidants during estivation under field conditions and to identify any effect of species on the biochemical responses of P. diplolister and P. cristiceps associated with estivation. To do so, we measured the activities of representative enzymes of intermediary metabolism and antioxidant systems, as well as glutathione and protein carbonyl levels, in the skeletal muscle of P. diplolister. Our findings revealed the suppression of oxidative metabolism and activation of antioxidant enzymes in estivating P. diplolister compared with active specimens. No changes in oxidative damage to proteins were observed and estivating P. diplolister had lower levels of disulfide glutathione (GSSG) and disulfide-to-total glutathione ratio (GSSG/tGSH) than those observed in active individuals. When data for P. diplolister and P. cristiceps were assembled and analyzed, significant effects of species were detected on the activities of metabolic enzymes (citrate synthase, isocitric dehydrogenase, malic enzyme and creatine kinase) and antioxidant enzymes (catalase, glutathione peroxidase and glutathione transferase), as well as on GSSG/tGSH ratio. Such effects might underlie the physiological and behavioral differences between these two species that share the same microhabitat and survival strategy (i.e., to estivate) during the dry season. Despite some peculiarities, which reflect the physiological diversity of the mechanisms associated with estivation in the Brazilian Caatinga, both P. diplolister and P. cristiceps seem to balance the suppression of oxidative pathways, the maintenance of the capacity of oxygen-independent pathways and the activation of endogenous antioxidants to preserve muscle function and be ready to resume activity whenever the unpredictable rainy period arrives.